Investigate the effect of honey on the absorption of seven active ingredients from wu‐tou decoction in rats. (27th January 2022) - Wang, Jia; Zheng, Shujing; Li, Yang; Hu, De; Hu, Liming; Wang, Shumin; Leng, Xiangyang
Abstract: Wu‐tou decoction has been used as a traditional Chinese medicine prescription for thousands of years. It comprises five herbs, namely Radix Aconiti Preparata, Ephedrae Herba, Astragali Radix, Glycyrrhiza Radix, and Paeoniae Radix Alba . In addition, the original prescription contains honey, but in modern research, the existence of honey is commonly ignored. The aim was to investigate the effect of absorption in rats after oral wu‐tou decoction with or without honey. In this research, a rapid and sensitive UPLC‐MS/MS method was investigated for the quantitative analysis of ephedrine, pseudoephedrine, paeoniflorin, calycosin‐7‐glucoside, glycyrrhizic acid, liquiritin, and benzoylmesaconine in rat plasma after single and continuous oral decoctions. The results of the pharmacokinetic parameters showed that C max, CL/F, AUC0– t, and AUC0–∞ in the honey group were significantly increased than those in the non‐honey group except for ephedrine and pseudoephedrine. The same trend was observed regardless of single or continuous oral administrations. Research studies showed that honey could promote the absorption of some effective components in wu‐tou decoction in rats, enhance bioavailability, and provide a theoretical basis for the scientific and rational compatibility of the original prescription.